Midiatização amazônica: a construção sistêmico-discursiva do Infoamazonia - Flôres, Vinícius dos Santos (2017)
The research problematizes communicational issues of environmental movements, according to the procedural mediatization scenario stimulated by information and communication technologies. Within this context, the aim of this work is to investigate the InfoAmazonia, database platform about the issues of transnational Amazon. The theoretical framework of the work consists in intertwining of studies about the phenomenon of mediatization (VERÓN, 2013; FAUSTO NETO, 2010a; GOMES, 2006), particularly in relation to the discursive approach, with a systemic-communicational constructivist perspective (LUHMANN, 2005). Similarly, permeates by issues of journalism in mediatization (SOSTER, 2009) and important concepts to the environmental context (LEFF, 2011). Thus, the general objective is to analyze how the discursive dynamics generated from problems of the Amazon rainforest engender the construction of InfoAmazonia. Specifically, we seek to map the supply chain to understand the complexity of the discursive tissue that forms the platform, to observe and to describe the operational dynamics of the database and understand how to systematize the complex discursive production of transnational Amazon. It is a study of exploratory case (YIN, 2005), descriptive and analytical, based on bibliographical, documentary and field research. The data collection period corresponded to one year of samples, from April 2015 to March 2016. The research is divided into three theoretical-methodological stages titled: Discursive mapping, Logics and constructive functionalities and Fragments of a tissue: the case of Tiquié river. Among the results, the case of InfoAmazonia showed fragments of continuous transformations provided by the mediatization process in society. The descriptive-observational analysis pointed that georeferentiality is one of the differentials of the systemic-discursive construction of the database. Therefore a decentralized re-reading of the scope of discoursive production is intensified by enabling the collaborative contribution on important themes in the contemporary world as the environmental ones, signaling in this aspect for the emergence of a singular social practice.